Implementing somatic mutation testing in clinical setting: recommendations from a panel of experts. - Cordeiro-de-Lima, Vladmir Cláudio; Araújo, Luiz Henrique; Garicochea, Bernardo; Rocha, Vanderson; Mano, Max; William, William Nassib; Chaves, Aline Lauda Freitas; Fernandes, Gustavo dos Santos; Nogueira-Rodrigues, Angelica; Jardim, Denis Leonardo; Melo, Andreia C; Mello, Celso Abdon; Baldotto, Clarissa Serodio; Zukin, Mauro; Calabrich, Aknar; Gelatti, Ana; deCastro, Gilberto, Jr; Bueno de-Oliveira, Thiago; Gifoni, Markus; Barra, Williams; Coutinho, Anelisa K.; Peixoto, Renata D'Alpino; Rameri de-Azevedo, Carla; Paulino, Eduardo; Bines, José; Barroso, Romualdo; Gimenes, Daniel; Kaliks, Rafael Aliosha; Fay, Andre Poisl; Bugano, Diogo; Isaacsson, Pedro; Chiattone, Carlos; Vaz, Jorge; Duffles, Guilherme; Baiocchi, Otavio; Schmerling, Rafael; Munhoz, Rodrigo Ramela; Guedes, Rodrigo; Feher, Olavo; Yamada, Camilla Akemi Felizardo; Fittipaldi, Carolina; Mathias, Clarissa Maria de Cerqueira; Clara, Renan Orsati; Leal, Alesssandro (Brazilian Journal of Oncology, 2021)
There has been a rapid increase in the volume of genomic data gathered from different cancers, this has helped to develop new tumor classifications as well as to select better tailored therapies for the patients. Some of the genomic markers identified are also prognostic and predictive factors. Additionally, many technologies have been used to investigate these alterations, each with different benefits and caveats. The Genomics Committee from the Sociedade Brasileira de Oncologia Clínica (SBOC) put together a group of specialists, from different regions of Brazil that work both in the private and public scenario, to gather and organize the information regarding the utility of somatic mutation testing in solid tumors. This special article summarizes their recommendations on how to better incorporate this information into clinical practice.
Keywords: Somatic mutation testing; Comprehensive genomic profiling; Genomic medi-cine; Precision oncology.